Death by A Thousand Cuts: Double Burden and Subordination of Female Ride-Hailing Drivers Towards Social Security Services - Aqilatul Layyinah; Eksanti Amalia Kusuma Wardhani (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2024)
Ride-hailing platforms have mushroomed ever since the digitalization and technology development occurred in Indonesia. This could absorb most of the workforce, one of which is the ride-hailing drivers. Nevertheless, the informality of ride-hailing drivers has put them in a vulnerable position, especially for female drivers. This study aims to reveal the regulatory loopholes of gig workers, not to mention the ride-hailing drivers, subordination and vulnerabilities towards female ride-hailing drivers in Indonesia, as well as the urgency and best practice of social security that should be provided for female ride-hailing drivers. The research method utilized in this study is Participatory Narrative Inquiry (PNI) by gathering personal stories of the research subject, female ride-hailing drivers, through in-depth interviews. This study found several critical issues: (i) regulatory loopholes that emerge under the partnership scheme, leaving no obligatory for the ride-hailing platforms to provide social security services; (ii) female ride-hailing drivers in Indonesia experienced subordination and vulnerabilities, including gender stereotyping, sexual harassment, double burden between care work and paid work, as well as the absence of employment basic rights and access to social security services; (iii) providing and expanding National Health Insurance (JKN) to childcare and elderly care, as well as Employment Insurance (JKK, JKM, JHT, and pension insurance/JP) may lighten up the burden of female ride-hailing drivers.